Sociolinguistic Exploration of Language and Society in 'The Bluest Eye' - Chaudhary, Anjum; AlZahrani, Sahar (International Journal of Language and Literary Studies, 2024)
The present study aims to investigate the sociolinguistic features surrounding “The Bluest Eyes”, a novel by Toni Morrison. In general, "The Bluest Eye" explores how cultural variables, particularly those about race, physical beauty, and identity, can affect the way people see themselves and the world. It is a compelling examination of the terrible and deeply personal effects that systematic racism and cultural beauty standards may have on individuals within a community. In an attempt to examine how societal dynamics are presented within a single-speech community, sociolinguistic literature has been reviewed. A thorough discourse analysis of the selected conversations of the fictional narrative is done using Hymes’ S-P-E-A-K-I-N-G model. The samples are taken from the primary text – ‘The Bluest Eyes’ as the major corpus. The findings indicate that social variables like cultural norms, age, gender, race, class, etc. are very much prevalent in the language of the characters and influence the communication competence of the characters in the social milieu presented by Toni Morrison. To prove the viability of Hymes’ proposition of the S-P-E-A-K-I-N-G model, the study may help teachers as well as learners to gain a better perception and understanding of any literary text. Moreover, it would be a useful guide to the analysis of the dimensions of communication.